OPTIMIZATION OF MODERN METHODS FOR DIAGNOSING HELMINTHIC AND PARASITIC INVASIONS IN CHILDREN - Medetbaeva A.D.; Daminov F.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Relevance: Helminthic and parasitic invasions, especially helminthiasis, are widespread among children. In our country, the most common helminthiases are nematodoses-parasitic diseases caused by roundworms (nematodes) that are transmitted through the fecal-oral route. The most well-known representatives of this group of helminths are Ascaris lumbricoides (roundworms), Enterobius vermicularis (pinworms), and Trichocephalus trichiurus (whipworms). Currently, helminthiases remain one of the major public health issues but are among the diseases that are least detected and inadequately assessed.